Electrodeposition of Nickel from its Sulphate Salt in a Ethylene Glycol— Water Mixture - SADEGHI SARABI, R.; MESHKATALSADAT, M.H.; DARGAHI, M.T. (Asian Journal of Chemistry, 2010)
The effect of different factors, such as current density (CD) and annealing temperatures, on cathode current efficiency (CCE), microhardness and quality of electrodeposited nickel which obtained from a bath containing 0.2 M nickel sulphate and 0.2 M boric acid as electrolyte and buffer respectively in a glycol-water mixture, was investigated. Bright and adherent nickel deposits with high CCE were produced at a CD of 2.0 Adm-2 and 30°C. The microhardness of the deposits decreased with increasing annealing temperature. The structural features of the deposits were examined by SEM and TEM. The results have been explained by taking into account the hydrogen content in the deposits.